Low-Temperature Performances for Monolithic V2O5-WO3/TiO2 Catalyst in the NH3-SCR System - Zhou, Song; Liu, Yan; Zhu, Yuan-Qing; Yu, Yan; Li, Cai-Ling (Asian Journal of Chemistry, 2013)
According to the working characteristics of marine diesel engines, a SCR catalyst testing system was developed and catalytic activities of an extruded commercial monolithic V2O5-WO3/TiO2 catalyst at low temperatures were studied in this paper. Meanwhile, key parameters including catalytic temperature, space velocity, NH3 consumption, excess O2 and NO2 concentration in the gas mixtures were also analyzed to enhance the low-temperature performances of marine SCR systems. It is found that desorption reaction of NH3 absorbed on the catalyst surface may be responsible for a sharply increasing of NH3 slip in a short time, which could also lead to the secondary pollution of NH3 from the SCR system.